A systematic review of organizational culture literature: Lessons from the past and avenues for future research (Lighthouse Publishing, 2023)
Organizational culture is an important factor in human and organizational behavior, but there are disagreements over its definitions and measurements. Previous research has demonstrated positive aspects associated with corporate culture, such as its role in the effective adoption of quality management and its importance in the organizational change process. It can affect workers' willingness to embrace a change process. The purpose of this study is to review the past literature on organizational and identify research issues that could influence the body of knowledge of organizational culture. A systematic review of literature was carried out using PRISMA method. Data was obtained from four databases and a total of 30 relevant journals were identify for further analyses. The study revealed that different conceptualization and operationalization of Organizational culture creates the inconsistencies in findings previous studies. The study developed a framework for determining choice of constructs in each cultural context.